An update on the occurrence of nematodes belonging to the genus Bursaphelenchus in the Mediterranean area - Errico, Giada (2016)
The genus Bursaphelenchus containsmore than100species ofnematodes. Knowledge of the occurrence ofnematodes belonging to this genus is a prerequisite for monitoring issues and control measures to prevent the introduction and establishment of pathogenic species such as Bursaphelenchus xylophilus into forest ecosystems. According to data collected from the published literature and databases such as Web of Science, FSTA, CAB Abstracts, Biological Abstracts and the EPPO Reporting Service, 22 Bursaphelenchus species have been recorded to be present in the Mediterranean region. These species are classified into nine morphological groups sensu Braasch, H., Burgermeister, W. and Gu, J. 2009 Revised intra-generic grouping of Bursaphelenchus Fuchs, 1937 (Nematoda: Aphelenchoididae). J.Nematode Morphol. Syst. 12, 65–88): abietinus, eggersi, eremus, fungivorus, hofmanni, kevini, leoni, sexdentati and xylophilus, although two species are currently not assigned to a specific group. Movement of insect vectors in international trade of wood and host plants into and within Mediterranean areas is consideredthemainpathwayfor Bursaphelenchus species dispersal.Manyof the species representasignificant risk for pine and possibly other forest types, an annotated check-list of Bursaphelenchus species in the Mediterranean area, their main features, pathogenicity, host plants and insect vectors is presented.